Preliminary study on the effectiveness of mosquito repelling lamp, E Da - Dhang, C.C.; Hadi, A.A.; Ibrahim, S.; Lim, L.H. (2007)
Photon (light) technology has already been widely used in make-up, medical treatment etc, but repelling mosquitoes by photon technology is an innovation. The objective of this study was to determine the efficacy of a mosquito repelling lamp, E Da under indoor conditions. E Da lamp is a lamp coated with yellow luminous pigment on the inner part of the glass bulb of the lamp which is used to screen out the UV radiation, and when it is turned on, the yellow illuminating wavelength will drive the mosquitoes away. The tests were conducted inside 2 cabins measuring 8'X 8'X 20'. The mosquito population was estimated by using the Bare Leg Catch (BLC) techniques. For treated test, E Da lamp was placed indoor 2 - 3 meters away from a human bait. Another cabin without the lamp was used as untreated control. BLC was conducted in both sites simultaneously. The mosquitoes collected in this study were solely those of Culex quinquefasciatus and Aedes aibopictus. There was an 91.34 reduction of Cx. quinquefasciatus population in the treated test compared with the untreated cabin during the 4 hours catches (p < 0.05). E Da mosquito repelling lamp used in this study exerted repellency effect against the mosquitoes especially Cx. quinquefasciatus.